PELAKSANAAN PENDIDIKAN KARAKTER DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU UKHUWAH BANJARMASIN - Ahmad Rusadi (JURNAL SOCIUS, 2014)
All this time the character education is still needed until now because of the declining moral continually occur in the generation of this nation and nearly brought the nation to a destruction, It is necessary to find repair solutions, one of which is to implement character education in the world of education. This research uses qualitative research, the procedure of data collection used were: Observation, interviews, and Library. The method of qualitative data analysis techniques through three stages, they were data reduction, data display and drawing conclusion. The results showed: The  Planning of character education shows that  all the teachers make learning program by entering values into the character of learning, holding management planning in improving the quality of education, and planning of student activities, the value obtained by the mandate, responsibility, humanity, nationalism, curiosity, logical thinking, critical, work hard, creative, independent, self-confidence, respect for diversity, tolerance, solidarity, care for the environment, patriotism, courtesy, collaboration, innovation, work hard and living clean behavior. The implementation of character education shows the teachers put character values to the students during the learning, conduct management and policy agenda in support of character education in schools , and organize student activities, the value obtained are the care each other, independent, sense of desire of knowledge, love of country, care about the environment, creative, innovative, work hard, respect for achievement, togetherness, available, self-contained, obey to social rules, respect for diversity, discipline, responsible, and Nationalist. Keywords: Implementation, and character education